Efeito de vernizes com alta e baixa concentração de fluoreto suplementado com trimetafosfato de sódio sobre a erosão da dentina bovina: estudo in vitro - Prado, Kamila Miranda [UNESP] (2013)
The current study evaluated the effectiveness of fluoride varnishes supplemented or not with sodium trimetaphosphate (TMP) on dentin erosion. After polished, 60 bovine dentin discs (4 x 4 mm diameter) were selected by the surface microhardness (SMH). Then, they were divided into 5 groups (n = 12) according to the type of varnish to be used: placebo (no F / TMP), 5% NaF varnish (5% NaF), 2.5% NaF varnish (2.5% NaF), 2.5% NaF varnish associated with 5% TMP (2.5% NaF + 5% TMP), 5% NaF varnish associated with 5% TMP (5% NaF + 5% TMP). The erosive challenge was promoted by citric acid (0.05 M, pH = 3.2) for a period of 5 days, for 5 minutes (4 times daily). Then, the dentin damage (μm) was determined after the challenge. To analyze the data, the experimental varnishes were considered as variation factor and the dentin surface damage (μm) as measurement variable. The results were submitted to variance analysis (one-criterion) followed by Student-Newman-Keuls test (p<0.05). The groups with the 2.5% NaF + 5% TMP and 5% NaF + 5%TMP showed lower damage values when compared to the other groups (p <0.05). The groups 2.5% NaF and 5% NaF showed similar damages (p> 0.05). Therefore, the results suggest that it is possible to reduce dentin erosive damage supplementing fluoride varnish with sodium trimetaphosphate